Hubungan Kecerdasan Moral dengan Sikap Sopan Santun Siswa Kelas Tinggi SDN Gugus I Kota Bengkulu - Gina Ramadani; Osa Juarsa; Feri Noperman (JURIDIKDAS, 2021)
This study aims to analyze the relationship between moral intelligence and courtesy attitudes of high-grade students of SDN cluster I, Bengkulu City. This research is a quantitative research. The research method used is correlation. The population in this study were high-grade students consisting of grades 4 and 5 of the Elementary School Cluster I of Bengkulu City, totaling 350 students consisting of 3 elementary schools, namely SDN 1, SDN 6, and SDN 7. The sample in this study used the simple random sampling technique. , the sample in this study amounted to 35 respondents who were drawn proportionally. The instruments and data collection techniques used in the study were a questionnaire consisting of a moral intelligence questionnaire and a courtesy questionnaire. The data analysis technique used the product moment correlation formula and the t test. The calculation results obtained rcount value of 0.562, greater than rtabel 0.334 with a significant level of tcount 3.892, and the contribution of moral intelligence by 32% to the polite attitudes of high class students of SDN cluster I Bengkulu City. Thus it can be concluded that there is a relationship between moral intelligence and courtesy attitudes of high-grade students of SDN cluster I Bengkulu City.